Pelindungan HAM dalam Mekanisme Pembubaran Ormas Berbadan Hukum Berdasarkan Undang-Undang No. 16 Tahun 2017 (Human Rights Protection on Dissolution Mechanism of Civil Society Organizations (CSOs) Based on Law No. 16 of 2007) - Marfuatul Latifah (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2020)
This article examines the legality of the issuance of Government Regulation in Lieu of Act, the protection of human rights for CSOs through court mechanisms, and the improvement of the rule of dissolution of CSOs in the future. In addition, this article also provides suggestions related to the improvement of dissolution mechanism of CSOs in the future. This article was prepared using the normative juridical method and descriptively described. The discussion on the issuance of Government Regulation in Lieu of Act on CSOs did not fulfill the elements of “urgency of force” and “potential danger” as governed in Article 22 and Article 12 of the 1945 Constitution of the Republic of Indonesia. The elimination of dissolution mechanism of CSOs through court hearings denied the protected rights of CSOs in Indonesia. Furthermore, this condition also does not reflect the principles of the rule of law which contain elements of due process of law. It was concluded that amendment to the provisions on dissolution of CSOs must start immediately. Consequently, the CSOs’ Bill must amend provisions on the dissolution of CSOs, namely the regulation on general dissolution of CSOs through trial with a maximum time limit of 150 days, whereas in “certain conditions” CSOs can be forced to immediately stop their activities and the government allowed to request dissolution of CSO with a maximum 75 days time limit. The CSOs’ Bill must regulates the definition of “certain conditions”, so there will not be any violations on its implementation. AbstrakArtikel ini mengkaji mengenai legalitas penerbitan Perppu, pelindungan HAM bagi Ormas melalui ketersediaan mekanisme pengadilan, dan arah perbaikan ketentuan pembubaran Ormas dimasa yang akan datang. Selain itu artikel ini juga memberikan usulan terkait dengan perbaikan kebijakan mekanisme pembubaran Ormas dimasa yang akan datang. Penulisan artikel ini disusun dengan menggunakan metode yuridis normatif yang diuraikan secara deskriptif. Dalam pembahasan, penerbitan Perppu Ormas tidak memenuhi unsur “kegentingan memaksa” dan “keadaan bahaya” yang terdapat di dalam Pasal 22 dan Pasal 12 UUD NRI Tahun 1945. Penghapusan mekanisme pembubaran ormas melalui sidang pengadilan, merupakan pembatalan terhadap upaya pelindungan HAM bagi Ormas di Indonesia. Selain itu kondisi ini juga tidak mencerminkan prinsip negara hukum yang di dalamnya mengandung unsur due process of law. Disimpulkan bahwa perubahan ketentuan terkait dengan pembubaran ormas harus segera dilakukan. Oleh karena itu, RUU Ormas harus memuat beberapa materi muatan dalam perubahan ketentuan pembubaran ormas, yaitu pengaturan pembubaran ormas secara umum melalui persidangan dengan batas waktu 150 hari, sedangkan dalam “kondisi tertentu” Ormas dapat langsung dibekukan kegiatannya dan pemerintah dapat mengajukan permohonan untuk membubarkan ormas dengan batasan waktu 75 hari. RUU Ormas harus mengatur definisi tentang “kondisi tertentu” dalam dinamika keormasan, agar tidak terjadi pelanggaran dalam pelaksanaannya.